NEW DATA ON THERMAL FLOW IN THE CENTRAL PART OF THE KOLA PENINSULA - Glaznev V.N.; Raevskii A.B.; Kukkonen I.T.; Jokinen J. (My University, 2004)
Geothermal studies in the central Kola Peninsula revealed the existence of anomalously low heat flows in the depth range of 0-1 km. The nature of such anomalous temperature behavior in the Earth's upper crust is related to paleoclimatic influence of the Valdaian glaciation, presumably characterized by the absence of thick ice cover during long intervals.